(untitled) (Stato, Chiese e pluralismo confessionale, 2019)
SOMMARIO: 1. Autonomia delle organizzazioni religiose e diritti dei singoli: il problema ‘classico’ del contemperamento - 2. Il problema del contemperamento dinanzi alla Corte di giustizia. I casi Vera Egenberger e JQ: stessa narrativa per due gemelli (in parte) diversi? - 3. Il profilo sostanziale delle decisioni: le dimensioni della libertà religiosa e il principio di non discriminazione - 4. Il profilo ordinamentale: Carta dei diritti e principi generali del diritto dell’Unione europea nel rapporto fra sistemi. Collective religious freedom and principle of non-discrimination in the ‘constitutional’ system of the European Union ABSTRACT: In the two recently handed down Judgments in the cases Vera Egenberger and JQ, the Court of Justice of the European Union for the first time interpreted Article 4, par. 2 of the Anti-discrimination Framework Directive (Directive 2000/78/EC) admitting a ‘religious exemption’ in favour of Churches and other religious organisation, and ruled on the horizontal application of the right not to be discriminated against in situations coming within the scope of EU law. The paper explores the substantive implications of those Judgments for the collective religious freedom and their contribution in clarifying the horizontal direct effect of the fundamental rights and principles enshrined in the Charter of Fundamental Rights of the European Union.